2013
DOI: 10.1590/abd1806-4841.20132042
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of patients with systemic lupus erythematosus and discoid lesions

Abstract: BACKGROUND It has been observed that patients with systemic lupus erythematosus and discoid lesions have a milder systemic disease. OBJECTIVE To compare the clinical, demographic and autoantibody profile of systemic lupus erythematosus patients with and without discoid lesions. METHODSWe carried out a retrospective study involving 288 systemic lupus erythematosus patients who met at least four classification criteria of the American College of Rheumatology for systemic lupus erythematosus, comparing the clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Plasma levels of cell-free heme are elevated in several hemolytic and chronic inflammatory diseases, such as sickle cell disease [ 35 , 41 , 42 ], lupus arthritis [ 64 ], malaria [ 65 ], and following treatment with widely used platinum-based anticancer drugs [ 66 ]. However, the role of heme in HIV associated co-morbidities has not been yet elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma levels of cell-free heme are elevated in several hemolytic and chronic inflammatory diseases, such as sickle cell disease [ 35 , 41 , 42 ], lupus arthritis [ 64 ], malaria [ 65 ], and following treatment with widely used platinum-based anticancer drugs [ 66 ]. However, the role of heme in HIV associated co-morbidities has not been yet elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the skin manifestations at TD, we found that those with discoid rashes were less likely to have subsequent LN overall. Several studies have reported that patients with SLE with mucocutaneous lesions tend to have less vital organ involvement [54,55]. A British study that included 241 patients with jSLE found that those without skin manifestations tended to have more haematological and renal involvement [56].…”
Section: Discussionmentioning
confidence: 99%
“…The median age at diagnosis of DLE is 30 years 1 . SLE appears in 17-30% presenting as only discoid lesions and discoid lesions appear in 8-28% of SLE 3,4,5 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been described as part of systemic lupus erythematosus (SLE) or in isolation in adults 1 . We report a case of severe haemolytic anaemia with discoid lesions that gave a clue to diagnosis and management.…”
Section: Introductionmentioning
confidence: 99%